2021
DOI: 10.1089/apc.2020.0235
|View full text |Cite
|
Sign up to set email alerts
|

Shortening “the Road” to Improve Engagement with HIV Testing Resources: A Qualitative Study Among Stakeholders in Rural Uganda

Abstract: In HIV-endemic areas, traditional healers are frequently used with, or instead of, biomedical resources for health care needs. Studies show healers are interested in and capable of supporting patients in the HIV care cascade. However, adults who receive care from healers have low engagement with HIV services. To achieve epidemic control, we must understand gaps between the needs of HIV-endemic communities and the potential for healers to improve HIV service uptake. This study's objective was to characterize st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Due to the traditional nature of the district, most Vhavenda people frequent traditional healers as their first point of care. Other researchers 3 share the same sentiment that people do not believe in Western medicine. They would rather go to a traditional healer than waste time coming to the health facility.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Due to the traditional nature of the district, most Vhavenda people frequent traditional healers as their first point of care. Other researchers 3 share the same sentiment that people do not believe in Western medicine. They would rather go to a traditional healer than waste time coming to the health facility.…”
Section: Discussionmentioning
confidence: 85%
“…Using traditional healers has been associated with delays in HIV diagnoses and also lead to reduced antiretroviral (ARV) adherence amongst people living with HIV. 3 Traditional healers believe that there is no HIV, and this impacts negatively on the management of HIV as they end up influencing their clients to believe that they can heal them. Contrary to these findings, is the study 4 conducted in Bangladesh, which revealed that the Kabiraji traditional healers in Bhabanipur and Jobra villages believe that they have healed many diseases, including HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research from rural Mozambique showed that many PWH utilize traditional healers, and that visiting a traditional healer exponentially prolongs time to HIV diagnosis [32]. Some have suggested that traditional healers might be able to improve uptake of HIV services among their clients [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional healers have been proposed as a community-based strategy for enhancing the HIV care cascade [14,15]. Collaboration with traditional healers could be particularly impactful in sub-Saharan Africa where the WHO estimates that 80% of the population seeks their services on a regular basis [16].…”
Section: Introductionmentioning
confidence: 99%